The Role of Financial Literature of SMEs in the Internationalization of Export Products - Achmad Mamduh; Imam Mukhlis; Danardana Murwani (Eduvest - Journal of Universal Studies, 2022)
This research is a literature study on financial literacy and the internationalization of SMEs. This study aims to discuss the role of SME financial literacy in the internationalization of export products. The research method used in this study is a qualitative descriptive method. The type of data used in this research is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of the study conclude that the role of SME financial literacy in the internationalization of export products is very important. Financial literacy is one of the important knowledge resources that increase the capacity, skills and expertise of individuals and companies to use technology effectively. Important aspects to consider in the internationalization of SMEs include entrepreneurship, finance and technology, SME resources, routines within the company, entrepreneurial knowledge and actions. All these aspects, especially financial literacy, are important to be considered by SMEs that will become Global SMEs and when assessing opportunities in foreign markets in export products.